Abschlussschwäche? Die closure des höfischen Romans zwischen Mediengeschichte und Kulturpoetik - Kragl, Florian (Poetica, 2020)
The article deals with the closure of the, mostly Middle High German, courtly romance, taking as primary example Heinrich von Veldeke's Eneide. 'Courtly closure' is defined as a slow and tenacious fading of narrative progression, by means of gradually transforming this progression into a virtually static state, namely, the description of an enduring courtly feast. It is argued that this way of bringing a romance or a novel to its end - unusual in the course of European literary history - is motivated by several factors. Amongst these, special attention is paid to media history (episodic narration, recital) and to cultural poetics (didactic qualities of the courtly romance).
CRIS-Team Scopus Importer:2021-04-19